"y'=\\sqrt{1-x^2}"
"y=\\int\\sqrt{1-x^2}dx"
"x=sinu, u=arcsinx,dx=cosudu"
"y=\\int cos^2udu=\\int \\frac {cos2u+1}{2}du=\\frac {cosusinu+u}{2}"
"y=\\frac {arcsinx+x\\sqrt{1-x^2}}{2}+C"
"y=\\sum^{\\infin}_{n=0} a_nx^n"
"y'=\\sum^{\\infin}_{n=1} na_nx^{n-1}=\\sqrt{1-x^2}"
"c+2\\sum^{\\infin}_{n=0} a_nx^n=arcsinx+x\\sum^{\\infin}_{n=1} na_nx^{n-1}"
"c+2\\sum^{\\infin}_{n=0} a_nx^n=arcsinx+\\sum^{\\infin}_{n=1} na_nx^n"
"arcsinx=c+2\\sum^{\\infin}_{n=0} a_nx^n-\\sum^{\\infin}_{n=1} na_nx^n"
"arcsinx=c+2a_0+\\sum^{\\infin}_{n=1}(2-n)a_nx^n"
"arcsin0=0\\implies c+2a_0=0"
Answer:
"arcsinx=\\sum^{\\infin}_{n=1}(2-n)a_nx^n"
"(arcsinx)'=\\sum ^{\\infin}_{n=1}n(2-n)a_nx^{n-1}=\\frac {1}{\\sqrt{1-x^2}}"
"(arcsin0)'=1=a_1"
"(arcsin0)'''=1\\implies a_3=-1\/6"
By same way we can get "a_4,a_5,..."
So:
"\\frac {\\pi}{6}=arcsin(1\/2)=\\frac {1}{2}+\\frac {1}{6}\\cdot\\frac {1}{2^3}+..."
Comments
Leave a comment